Tinjauan Hukum Islam Terhadap Merarik Nyongkolan (Study Kasus di Desa Bajur Kec. Labuapi Lobar) - Badarudin (TAFAQQUH, 2024)
This study examines the Merarik Nyongkolan tradition in the Sasak community of Bajur Village, Labuapi District, West Lombok, from an Islamic legal perspective. The tradition, which involves the "elopement" of the bride and a Nyongkolan procession, has often been questioned regarding its conformity with Islamic law. The research utilizes a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews with community leaders, religious scholars, and married couples and direct observation of the Nyongkolan procession. The findings reveal that while most of the community supports the preservation of this tradition, debates arise concerning certain elements that are perceived as inconsistent with Islamic principles, such as the "elopement" of the bride and the public, festive parades. The contribution of this research lies in its in-depth explanation of how the Sasak community strives to balance the preservation of local culture with adherence to Islamic law. It also recommends adapting the tradition to align more closely with religious values without losing its cultural identity.